2019
DOI: 10.1212/wnl.0000000000007133
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation in early Alzheimer trajectory is associated with higher gray matter volume

Abstract: ObjectiveTo investigate the influence of microglial activation in the early stages of Alzheimer's disease trajectory, we assessed the relationship between microglial activation and gray matter volume and hippocampal volume in patients with mild cognitive impairment (MCI).MethodsIn this study, 55 participants (37 with early stages of MCI and 18 controls) underwent [11C]PBR28 PET, a marker of microglial activation; volumetric MRI to evaluate gray matter and hippocampal volumes as well as clinical and neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 60 publications
3
56
1
Order By: Relevance
“…conditions preceding the onset of dementia and alphasynucleinopathies, respectively 28,29 . In addition, Femminella et al 30 showed that increased microglial activation as measured with [ 11 C]-PBR28 PET in MCI subjects was associated with higher grey matter and hippocampal volume, suggesting that neuroinflammation is again involved in early stages of the disease or may even play a protective role in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…conditions preceding the onset of dementia and alphasynucleinopathies, respectively 28,29 . In addition, Femminella et al 30 showed that increased microglial activation as measured with [ 11 C]-PBR28 PET in MCI subjects was associated with higher grey matter and hippocampal volume, suggesting that neuroinflammation is again involved in early stages of the disease or may even play a protective role in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the two classic diagnostic hallmarks of AD, Aβ plaques and neurofibrillary tangles, the brain of patients with AD exhibits evidence of a sustained inflammatory response ( Mandrekar and Landreth, 2010 ; Femminella et al, 2018 , 2019 ). In the acute phase, inflammation in the brain represents an established defense against infections, toxins, and injury.…”
Section: Neuroinflammation In the Pathogenesis Of Alzheimer’s Diseasementioning
confidence: 99%
“…However, a long-standing pro-inflammatory and pro-oxidant environment sustained by persistent microglia activation is detrimental as it may contribute to neurodegeneration. This is particularly relevant in the context of Alzheimer's (AD) and Parkinson's disease (PD) [7,8]. Metabolic changes in microglia have also been associated with a state of chronic low-grade inflammation observed during aging (i.e., inflamm-aging) [9,10].…”
Section: Introductionmentioning
confidence: 99%